Impact of Adjuvant and Neoadjuvant Chemotherapy on BMI of Patients With Non-Metastatic Breast Cancer in Center of High Complexity Oncology in Southern Brazil (Global Journal of Medical Research, 2022)
Background Weight changes during chemotherapy in women with cancer breast cancer are commonly suggested by the medical literature The association between gain weight and chemotherapy has shown a general trend of decreasing magnitude in last years The consequence on disease-free survival and self-esteem in patients with breast cancer after chemotherapy highlights the importance of research on the topic This study aims to evaluate weight changes in patients with non-metastatic breast cancer undergoing adjuvant and or neoadjuvant chemotherapy in a oncology in southern Brazil Methods Data from 122 medical records center of high complexity oncology in Southern Brazil for patients diagnosed with non- metastatic malignant breast cancer and undergoing chemotherapy for one year Statistical analysis was performed by SPSS v 20 0
Keywords: adjuvant therapy; neoadjuvant therapy; body weight; body mass index; breast cancer